Cost-effectiveness of albumin in the treatment of decompensated cirrhosis in resource-limited healthcare settings - Irsan Hasan; Ignatia Sinta Murti; Putut Bayupurnama; Kemal Fariz Kalista; Christina Hill-Zabala; Dennis Kananda; Elisabet Viayna (BioExcel Publishing Ltd, 2024)
Background: Human albumin (HA) is an effective adjuvant treatment for patients with cirrhosis developing spontaneous bacterial peritonitis (SBP), hepatorenal syndrome (HRS) and ascites requiring large-volume paracentesis (LVP). However, cost remains a barrier to use, particularly in resource-limited settings. This study aims to assess the cost-effectiveness of HA in patients with cirrhosis with SBP, HRS or ascites requiring LVP in the Indonesian healthcare system as a representative of a resource-limited setting. Methods: Three decision-tree models were developed to assess the cost-effectiveness of (1) antibiotics and HA versus antibiotics alone in patients with SBP, (2) terlipressin and HA versus terlipressin alone in patients with HRS, and (3) LVP and HA versus LVP and gelatine for patients with ascites. Clinical utility and economic inputs were pooled from the available literature. Time horizon was 3 months. Outcomes were expressed as incremental cost-effectiveness ratios (ICER) reported as 2021 IDR per quality-adjusted life year (QALY) (exchange rate June 30, 2021: 1 EUR = 17,245 IDR). Willingness-to-pay thresholds considered were: three times the GDP per capita (199,355,561 IDR/QALY; 11,560 EUR/QALY) and one time the GDP per capita (66,451,854 IDR/QALY; 3853 EUR/QALY). Results: The ICER for antibiotics and HA (versus antibiotics alone) for SBP was 80,562,652 IDR per QALY gained (4672 EUR/QALY). The ICER for terlipressin and HA (versus terlipressin) for HRS was 23,085,004 IDR per QALY gained (1339 EUR/QALY). The ICER for LVP and HA versus LVP and gelatine was 24,569,827 IDR per QALY gained (1425 EUR/QALY). Conclusion: Adjunctive HA may be a cost-effective treatment for SBP, HRS and LVP in resource-limited settings.